Effect of the local electricity mix on the environmental footprint of the initial stage of electrofuel production process - Perčić Maja; Caldogno Riccardo; Demetriou Marilena; Vladimir Nikola (E3S Web of Conferences)
The reliance on fossil fuels in the shipping sector has significant negative impacts on both the environment and human health. Electrofuels (e-fuels), produced by combining hydrogen and carbon using electricity, have emerged as a promising alternative. This paper investigates the influence of electricity sources on the environmental performance of e-fuel production, using Life Cycle Assessment (LCA) with a system boundary set at the initial co-electrolysis stage. The study examines four impact categories: climate change, terrestrial acidification, fine particulate matter formation, and human health toxicity (cancer). To assess the impact of different electricity sources, LCA was conducted for 12 distinct electricity production mixes from various countries and regions. As expected, the results indicate that countries relying predominantly on renewable energy sources achieve the lowest environmental impacts across all categories, which has been quantified here. Nuclear energy, although not renewable, also contributes to a reduced environmental footprint due to its low direct emissions. In contrast, electricity mixes with a high proportion of fossil fuels lead to significantly elevated environmental impacts. These findings highlight the importance of clean energy sources in maximizing the environmental benefits of e-fuels. This work has been funded by the European Union under grant number 101083700 (E-TANDEM).